Future Time Perspective, Risk Appetite, Pension Planning, and Retirement Saving Behavior Among Construction Service Entrepreneurs - R Heru Kristanto HC; Nilmawati Nilmawati; R. Hendry Gusaptono (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Saving and pension funds are effective methods for supporting future life, especially for SMEs that lack access to pension insurance. This study analyzes the impact of future time perspective, risk appetite, and pension planning on retirement saving behavior, with gender as a moderating variable. Data were collected from 102 construction service entrepreneurs in Yogyakarta, Indonesia. Using a quantitative approach, the data were analyzed using moderation regression with SEM-PLS. The results indicate that future time perspective has a positive effect on retirement saving behavior (O = 0.180, p = 0.045). Risk appetite does not affect retirement saving behavior (O = -0.338, p = 0.053). Pension planning has a positive effect on retirement saving behavior (O = 0.696, p = 0.000). Gender significantly moderates the effects of future time perspective (O = 0.781; p = 0.000), risk appetite (O = 0.454; p = 0.022), and pension planning (O = -0.618; p = 0.000) on retirement saving behavior. This model has a high level of suitability in explaining the retirement saving behavior (Q2 = 0.618). The results emphasize the importance of future awareness, risk considerations, and understanding of financial planning and retirement in shaping savings behavior.